Muslim Elderly Care based on Maqasid Shariah A Case Study of Pahang State, Malaysia - Hasiah, Mat Salleh; Norazmi, Anas; Siti Marsitah, Mohd Mokhtar; Norhapizah, Mohd Burhan; Rashidi, Abbas (Human Resource Management Academic Research Society (HRMARS), 2022)
There has been an increased number of elder abuse cases in recent years due to ageing populations in many countries. As emerging evidence indicates, the prevalence of abuse and neglect of older people in our country reflects the heirs' and descendants' failure to apply the Islamic principle of maqasid shariah (Objective of Shariah) in caring for Muslim elderly people, which is strongly supported by Islam. From this point of departure, the purpose of this study is to examine the care for elderly Muslim citizens based on the established principle of maqasid shariah, as well as the support and charity issues associated with the Muslim elderly, with special consideration given to the Senior Citizens Activity Center (PAWE)Pahang Darul Makmur. A qualitative case study design was used in the current study involving officers or administrators of the Senior Citizens Activity Center (PAWE) in a district of Pahang state using a semi-structured interview instrument. The sample was purposely selected from seven districts in Pahang, the Bera, Cameron Highland, Jengka, Maran, Muadzam, Raub, and Temerloh districts. An analysis of the interview findings was conducted using content analysis. As a result of this study, PAWE is recognized as an important institution for elderly care activities and fulfilling leisure time following the principle of maqasid shariah. The responsibility of supporting parents, especially the elderly, lies with their children. The assistance provided by other institutions and bodies, such as the Department of Community Welfare (JKM), serves only as additional support in achieving the goals of the Senior Citizens Policy (DWEN).